RETRACTED: Study on the Effect of Oral Administration of Bacteriophages in Charles Foster Rats With Special Reference to Immunological and Adverse Effects - Gangwar, Mayank; Rastogi, Sonam; Singh, Digvijay; Shukla, Alka; Dhameja, Neeraj; Kumar, Deepak; Kumar, Rajesh; Nath, Gopal (Frontiers in Pharmacology, 2021)
Numerous pre-clinical and clinical studies have recently demonstrated the significant role of phage therapy in treating multidrug-resistant bacterial infections. However, only a few researchers have focused on monitoring the phage-mediated adverse reactions during phage therapy. Besides adverse reactions, immunological response after short- and long-term oral administration of bacteriophages is also lacking. In this study, we administered the bacteriophages orally against Klebsiella pneumoniae XDR strain in dosages of 1015 PFU/mL and a 1020 PFU/mL (still higher) to Charles Foster rats as a single dose (in acute toxicity study) and daily dosage for 28 days (in sub-acute toxicity study). One milliliter suspension of bacteriophages was administered through the oral gavage feeding tube. No adverse effect was observed in any of the experimental as well as in the control animals. Further, an insignificant change in food and water intake and body weight was observed throughout the study period compared with the control group rats. On the 28th day of phage administration, blood was collected to estimate haematological, biochemical, and cytokines parameters. The data suggested no difference in the haematological, biochemical, and cytokine profile compared to the control group. No significant change in any of the treatment groups could be observed on the gross and histopathological examinations. The cytokines estimated, interleukin-1 beta (IL-1β), IL-4, IL-6, and INF-gamma, were found within the normal range during the experiment. The results suggested no adverse effect, including the severe detrimental impact on oral administration of high (1015 PFU/mL) and very high dose (1020 PFU/mL) of the bacteriophages cocktail. The high and long-term oral administration of bacteriophages did not induce noticeable immunological response as well.